CAUSES OF ORPHANS AND SOCIAL ORPHANS, AND WAYS TO ELIMINATE THEM - S.B. Sobirov; L.T. Torakulov; Hayitboyev Sanjar (Galaxy International Interdisciplinary Research Journal, 2022)
Today’s demand and one of its urgent tasks is to provide social protection for the health, moral and spiritual development of orphans and orphans. This can be seen from the personal documents of the students during the conducted scientific research. It has been shown that 65 percent of children have somatic and mental diseases. There are children with chronic diseases in which the functional withdrawal of the organism is up to 10% in grades 1-3, 30% in grades IV-VIII, and 70% in grades IX-XI. When comparing the children of the above 3 groups with the children raised in the family, the proportion of children suffering from this disease is 10 percent. 70% of children of the same age are often found to be suffering from complicated nervous diseases such as anxiety, fear, narcissism, laziness, mischievousness due to the derailment of higher and nervous system activity.